Stormin' Normans (Horrible Histories) - Terry Deary (UK Scholastic, 2001)
This title contains fascinating facts about Bill the Conquerer and his bully boys who battled at Hastings, stormed around Europe and joined the Crusades. There are tales of limb-chopping, terribly tortured saints and you can find out what "really" happened in 1066.